The effects of simultaneous isometric and eccentric- or concentric-biased exercise on cardiovascular and muscular health of young individuals - A. W. Baross; B. H. Wright; D. A. Langdon; A. D. Kay; M. Cauchi; A. Clarke; B. Pitham; C. Willmont; T. Barnett; C. Key; M. Reynolds; A. Thomas; et al. (European Journal of Applied Physiology, 2026)

Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Siderophore production and utilization by marine bacteria in the North Pacific Ocean - Jiwoon Park; Bryndan P. Durham; Rebecca S. Key; Ryan D. Groussman; Zinka Bartolek; Paulina Pinedo‐Gonzalez; Nicholas J. Hawco; Seth G. John; Michael C. G. Carlson; Debbie Lindell; Lauren W. Juranek; Sara Ferrón; et al. (Limnology and Oceanography, 2023)
Siderophores are strong iron‐binding molecules produced and utilized by microbes to acquire the limiting nutrient iron (Fe) from their surroundings. Despite their importance as a component of the iron‐binding ligand pool in seawater, data on the distribution of siderophores and the microbes that use them are limited. Here, we measured the concentrations and types of dissolved siderophores during two cruises in April 2016 and June 2017 that transited from the iron‐replete, low‐macronutrient North Pacific Subtropical Gyre through the North Pacific Transition Zone (NPTZ) to the iron‐deplete, high‐macronutrient North Pacific Subarctic Frontal Zone (SAFZ). Surface siderophore concentrations in 2017 were higher in the NPTZ (4.0–13.9 pM) than the SAFZ (1.2–5.1 pM), which may be partly attributed to stimulated siderophore production by environmental factors such as dust‐derived iron concentrations (up to 0.51 nM). Multiple types of siderophores were identified on both cruises, including ferrioxamines, amphibactins, and iron‐free forms of photoreactive siderophores, which suggest active production and use of diverse siderophores across latitude and depth. Siderophore biosynthesis and uptake genes and transcripts were widespread across latitude, and higher abundances of these genes and transcripts at higher latitudes may reflect active siderophore‐mediated iron uptake by the local bacterial community across the North Pacific. The variability in the taxonomic composition of bacterial communities that transcribe putative ferrioxamine, amphibactin, and salmochelin transporter genes at different latitudes further suggests that the microbial groups involved in active siderophore production and usage change depending on local conditions.

Alternative tissue fixation for combined histopathological and molecular analysis in a clinically representative setting - Amelia Meecham; Elena Miranda; Hayley T. Morris; Jane Hair; Karin A. Oien; Gareth Gerrard; Naomi Guppy; David Mooney; Emily C. Shaw; Margaret Ashton-Key; Robert Lees; Adrienne Flanagan; et al. (Histochemistry and Cell Biology, 2021)
Formalin is the principal tissue fixative used worldwide for clinical and research purposes. Despite optimal preservation of morphology, its preservation of DNA and RNA is poor. As clinical diagnostics increasingly incorporates molecular-based analysis, the requirement for maintaining nucleic acid quality is of increasing importance. Here we assess an alternative non-formalin-based tissue fixation method, PAXgene Tissue system, with the aim of better preserving nucleic acids, while maintaining the quality of the tissue to be used for vital existing diagnostic techniques. In this study, these criteria are assessed in a clinically representative setting. In total, 203 paired PAXgene Tissue and formalin-fixed samples were obtained. Blind-scored haematoxylin and eosin (H&E) sections showed comparable and acceptable staining. Immunohistochemistry (IHC) staining was suboptimal using existing protocols but improved with minor method adjustment and optimisation. Quality of DNA and RNA was significantly improved by PAXgene tissue fixation [RIN 2.8 versus 3.8 ( p < 0.01), DIN 5.68 versus 6.77 ( p < 0.001)], which translated into improved performance on qPCR assay. These results demonstrate the potential of PAXgene Tissue to be used routinely in place of formalin, maintaining adequate histological staining and significantly improving the preservation of biological molecules in the genomic era.

Physical activity in relation to circulating hormone concentrations in 117,100 men in UK Biobank - Eleanor L. Watts; Aurora Perez-Cornago; Aiden Doherty; Naomi E. Allen; Georgina K. Fensom; Sandar Tin Tin; Timothy J. Key; Ruth C. Travis (Cancer Causes & Control, 2021)
Purpose Physical activity may reduce the risk of some types of cancer in men. Biological mechanisms may involve changes in hormone concentrations; however, this relationship is not well established. Therefore, we aimed to investigate the associations of physical activity with circulating insulin-like growth factor-I (IGF-I), sex hormone-binding globulin (SHBG, which modifies sex hormone activity), and total and free testosterone concentrations, and the extent these associations might be mediated by body mass index (BMI). Methods Circulating concentrations of these hormones and anthropometric measurements and self-reported physical activity data were available for 117,100 healthy male UK Biobank participants at recruitment. Objectively measured accelerometer physical activity levels were also collected on average 5.7 years after recruitment in 28,000 men. Geometric means of hormone concentrations were estimated using multivariable-adjusted analysis of variance, with and without adjustment for BMI. Results The associations between physical activity and hormones were modest and similar for objectively measured (accelerometer) and self-reported physical activity. Compared to men with the lowest objectively measured physical activity, men with high physical activity levels had 14% and 8% higher concentrations of SHBG and total testosterone, respectively, and these differences were attenuated to 6% and 3% following adjustment for BMI. Conclusion Our results suggest that the associations of physical activity with the hormones investigated are, at most, modest; and following adjustment for BMI, the small associations with SHBG and total testosterone were largely attenuated. Therefore, it is unlikely that changes in these circulating hormones explain the associations of physical activity with risk of cancer either independently or via BMI.

Multi-stressor Effects of Ultraviolet Light, Temperature, and Salinity on Louisiana Sweet Crude Oil Toxicity in Larval Estuarine Organisms - Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Kaitlin Aaby; Deanna Hausman; Cheldina Jean; Paul L. Pennington; Emily C. Pisarski; Edward F. Wirth (Archives of Environmental Contamination and Toxicology, 2021)

Kinematic and Somatosensory Gains in Infants with Cerebral Palsy After a Multi-Component Upper-Extremity Intervention: A Randomized Controlled Trial - Nathalie L. Maitre; Arnaud Jeanvoine; Paul J. Yoder; Alexandra P. Key; James C. Slaughter; Helen Carey; Amy Needham; Micah M. Murray; Jill Heathcock; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; et al. (Brain Topography, 2020)

Neonatal Multisensory Processing in Preterm and Term Infants Predicts Sensory Reactivity and Internalizing Tendencies in Early Childhood - Nathalie L. Maitre; Alexandra P. Key; James C. Slaughter; Paul J. Yoder; Mary Lauren Neel; Céline Richard; Mark T. Wallace; Micah M. Murray (Brain Topography, 2020)
Multisensory processes include the capacity to combine information from the different senses, often improving stimulus representations and behavior. The extent to which multisensory processes are an innate capacity or instead require experience with environmental stimuli remains debated. We addressed this knowledge gap by studying multisensory processes in prematurely born and full-term infants. We recorded 128-channel event-related potentials (ERPs) from a cohort of 55 full-term and 61 preterm neonates (at an equivalent gestational age) in response to auditory, somatosensory, and combined auditory-somatosensory multisensory stimuli. Data were analyzed within an electrical neuroimaging framework, involving unsupervised topographic clustering of the ERP data. Multisensory processing in full-term infants was characterized by a simple linear summation of responses to auditory and somatosensory stimuli alone, which furthermore shared common ERP topographic features. We refer to the ERP topography observed in full-term infants as “typical infantile processing” (TIP). In stark contrast, preterm infants exhibited non-linear responses and topographies less-often characterized by TIP; there were distinct patterns of ERP topographies to multisensory and summed unisensory conditions. We further observed that the better TIP characterized an infant’s ERPs, independently of prematurity, the more typical was the score on the Infant/Toddler Sensory Profile (ITSP) at 12 months of age and the less likely was the child to the show internalizing tendencies at 24 months of age. Collectively, these results highlight striking differences in the brain’s responses to multisensory stimuli in children born prematurely; differences that relate to later sensory and internalizing functions.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Dietary greenhouse gas emissions of meat-eaters, fish-eaters, vegetarians and vegans in the UK - Peter Scarborough; Paul N. Appleby; Anja Mizdrak; Adam D. M. Briggs; Ruth C. Travis; Kathryn E. Bradbury; Timothy J. Key (Climatic Change, 2014)

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Application of metabolomics to understanding biofilms in water distribution systems: a pilot study - D.J. Beale; R. Barratt; D.R. Marlow; M.S. Dunn; E.A. Palombo; P.D. Morrison; C. Key (Biofouling, 2013)

Anthropometric characteristics and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Fatemeh Saberi Hosnijeh; Isabelle Romieu; Valentina Gallo; Elio Riboli; Anne Tjønneland; Jytte Halkjær; Guy Fagherazzi; Françoise Clavel-Chapelon; Laure Dossus; Annie Lukanova; Rudolf Kaaks; Antonia Trichopoulou; et al. (Cancer Causes & Control, 2013)

Marine atmospheric boundary layer over some Southern Ocean fronts during the IPY BGH 2008 cruise - C. Messager; S. Speich; E. Key (Ocean Science, 2012)
A set of meteorological instruments was added to an oceanographic cruise crossing the Southern Ocean from Cape Town to 57°33' S during the summer of 2008. The Cape Cauldron, the Subtropical, Subantarctic, Polar and southern Antarctic Circumpolar current fronts were successively crossed. The recorded data permitted to derive the exchange of momentum, heat and water vapour at the ocean-atmosphere interface. A set of 38 radiosonde releases complemented the dataset. The marine atmospheric boundary layer characteristics and air-sea interaction when the ship crossed the fronts and eddies are discussed. The specific role of the atmospheric synoptic systems advection on the air-sea interaction over these regions is highlighted. Additionally, the Subantarctic front mesoscale variability induced an anticyclonic eddy considered as part of the Subantarctic front. The specific influence of this Agulhas ring on the aloft atmosphere is also presented.

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

Recent range expansions in non-native predatory beetles on sub-Antarctic South Georgia - P. Convey; R. S. Key; R. J. D. Key; M. Belchier; C. L. Waller (Polar Biology, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Partitioning of major and trace inorganic contaminants in fly ash acid mine drainage derived solid residues - W. M. Gitari; L. F. Petrik; D. L. Key; C. Okujeni (International Journal of Environmental Science and Technology, 2010)

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Effects of chemically spiked sediments on estuarine benthic communities: a controlled mesocosm study - W. L. Balthis; J. L. Hyland; M. H. Fulton; P. L. Pennington; C. Cooksey; P. B. Key; M. E. DeLorenzo; E. F. Wirth (Environmental Monitoring and Assessment, 2010)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

The effects of peroxovanadate and peroxovanadyl on glucose metabolism in vivo and identification of signal transduction proteins involved in the mechanism of action in isolated soleus muscle - Ricado Key Yamazaki; Sandro M. Hirabara; Osvaldo Tchaikovski; Maria Cecília Pascoal Lopes; Claudia Nogata; Júlia Aikawa; Everson A. Nunes; Ricardo A. Tanhoffer; Maurício D. Lissa; L. C. Fernandes (Molecular and Cellular Biochemistry, 2005)

Surface Water Pesticide Movement from the Dade County Agricultural Area to the Everglades and Florida Bay via the C-111 Canal - M. H. Fulton; G. I. Scott; M. E. DeLorenzo; P. B. Key; D. W. Bearden; E. D. Strozier; C. J. Madden (Bulletin of Environmental Contamination and Toxicology, 2004)

Dynamical and microphysical characteristics of Arctic clouds using integrated observations collected over SHEBA during the April 1998 FIRE.ACE flights of the Canadian Convair - I. Gultepe; G. A. Isaac; J. Key; J. Intrieri; D. O?C. Starr; K. B. Strawbridge (Meteorology and Atmospheric Physics, 2004)

The transcript abundance of GmGT-2, a new member of the GT-2 family of transcription factors from soybean, is down-regulated by light in a phytochrome-dependent manner - Kevin O'Grady; Virginia H. Goekjian; C. Joseph Nairn; Ron T. Nagao; Joe L. Key (Plant Molecular Biology, 2001)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

Increasing incidence of colon and rectal cancer among Hispanics and American Indians in New Mexico (United States), 1969-94 - Ann Chao; Frank D. Gilliland; William C. Hunt; Marc Bulterys; Thomas M. Becker; Charles R. Key (Cancer Causes & Control, 1998)